The Phaseolus vulgaris ZIP gene family: identification, characterization, mapping, and gene expression - Astudillo, Carolina; Fernandez, Andrea; Blair, Matthew W.; Cichy, Karen A. (Frontiers in Plant Science, 2013)
Zinc is an essential mineral for humans and plants and is involved in many physiological and biochemical processes. In humans, Zn deficiency has been associated with retarded growth and reduction of immune response. In plants, Zn is an essential component of more than 300 enzymes including RNA polymerase, alkaline phosphatase, alcohol dehydrogenase, Cu/Zn superoxidase dismutase, and carbonic anhydrase. The accumulation of Zn in plants involves many genes and characterization of the role of these genes will be useful in biofortification. Here we report the identification and phlyogenetic and sequence characterization of the twenty three members of the ZIP (ZRT, IRT like protein) family of metal transporters and three transcription factors of the bZIP family in Phaseolus vulgaris L. Expression patterns of seven of these genes were characterized in two bean genotypes (G19833 and DOR364) under two Zn treatments. Tissue analyzed included roots and leaves at vegetative and flowering stages, and pods at 20 days after flowering. Four of the genes, PvZIP12, PvZIP13, PvZIP16, and Pv bZIP1, showed differential expression based on tissue, Zn treatment, and/or genotype. PvZIP12 and PvZIP13 were both more highly expressed in G19833 than DOR364. PvZIP12 was most highly expressed in vegetative leaves under the Zn (-) treatment. PvZIP16 was highly expressed in leaf tissue, especially leaf tissue at flowering stage grown in the Zn (-) treatment. Pv bZIP1 was most highly expressed in leaf and pod tissue. The 23 PvZIP genes and three bZIP genes were mapped on the DOR364 x G19833 linkage map. PvZIP12, PvZIP13 and PvZIP18, Pv bZIP2, and Pv bZIP3 were located near QTLs for Zn accumulation in the seed. Based on the expression and mapping results, PvZIP12 is a good candidate gene for increasing seed Zn concentration and increase understanding of the role of ZIP genes in metal uptake, distribution and accumulation of zinc in P. vulgaris.